The little book of being eaudiobook Practices and guidance for uncovering your natural awareness. - Winston, Diana (Tantor Media, 2019)
Do you recall, as a child, being enthralled by a drifting cloud, the babbling of a stream, the wandering of a ladybug? If so, then you've already had a taste of natural awareness. Known and revered in many contemplative traditions, natural awareness transcends even these wondrous childhood moments. It has been described as a profound "awareness of awareness"—an effortless and panoramic state of fully being at our deepest levels. Created for those new to meditation and long–time meditators alike, The Little Book of Being shows us how to discover this free–flowing and expansive side of mindfulness—no formal sitting practice required. This concise and friendly guide takes us through 73 "mini–chapters" that explain natural awareness and help us experience it via simple and enjoyable explorations to bring welcome moments of peace, connection, and spaciousness to our often distracted and stressful lives.